EVALUATION OF ENERGY PERFORMANCE USING DOE-2 ENERGY SIMULATION PROGRAM IN SINGAPORE - Po Seng Kian (DIMENSI (Journal of Architecture and Built Environment), 2000)
Recently, due to worldwide energy cost rising significantly, there has been an essential need to minimize the energy consumption. This global warning address many countries including Singapore realizing the important of energy efficiency in industries and buildings. This paper deals with analyzing the energy consumption of an 11-storey commercial building in Singapore using DOE-2 Energy Simulation Program. A study is made on the benefits derived from modifying the building envelope, space system setting, air-conditioning plant, and lighting. This encompasses a description of its quantitative impact on cooling load, energy consumption and energy saving achieved as compared with the original building. Following this, a life cycle costing is done to determine the economic benefits attained from this modification. This study shows that some alternative solutions can be achieved using energy simulation program to conserve the energy consumption.